Representasi Masyarakat Aktif di Masa Pandemi Covid-19 (Studi Ekonomi dan Sosial Keberagamaan di Bausasran Danurejan Yogyakarta) - Ratna Istriyani; Muhammad Fathur Rahman (Jurnal Penelitian, 2020)
The purpose of this study consists of two points. First, explore the responses and strategies of the Bausasran community in overcoming economic problems due to the Covid-19 pandemic. Second, reviewing the religious ritual protocol of the Bausasran community during the Covid-19 pandemic. The method used in this research is descriptive qualitative. Collecting data was used two tecniques, that were observation and interview. Both of tecniques were did in accordance with health protocols in a pandemic situation.Based on the results of research conducted, community of Bausasran Yogyakarta were able to overcome the problem of food security, especially for economically vulnerable groups due to the pandemic. A strategy was carried out through a food packets distribution movement. The distribution of food packets carried out by the community for residents who lost their source of income during the pandemic. The funds of food packets were obtained from compulsory contributions made by residents every month through the RT and RW management. Then in the socio-religious aspect, local leaders together with residents made worship protocols for worshipers at the mosque according to the appeal of the Indonesian Ministry of Religion. In addition, it eliminated crowd routine religious activities. Based on this, it can be concluded that the local initiation from the Bausasran community in Yogyakarta is a representation of the active society, described by Amitai Etzioni who utilizes three factors: knowledge, decision making, and power.